Protection Levels after Fault Exclusion for Advanced RAIM. Issue 4 (6th December 2017) - Blanch, Juan; Walter, Todd; Enge, Per
Abstract: We present a fault exclusion algorithm and a formula for the position error bounds after an exclusion event for Advanced Receiver Autonomous Integrity Monitoring. This algorithm has both a low computational load and an analytical proof of integrity. To mitigate the loss of performance associated with false exclusion, the method both exploits the ambiguity as to which measurement must be excluded and a pre‐allocation of the integrity budget to the exclusion outcomes. The algorithm is evaluated for a GPS‐Galileo Advanced RAIM scenario. We show that with this algorithm, the addition of the exclusion option does not impact the protection levels compared to detection only and that when the faults are large enough, the effect on the user is equivalent to the effect of an outage. Copyright © 2017 Institute of Navigation